A systematic review and meta-analysis of Cryptosporidium prevalence in deer worldwide. (August 2021) - Lv, Xiao-Qin; Qin, Si-Yuan; Lyu, Chuang; Leng, Xue; Zhang, Ji-Fa; Gong, Qing-Long
Highlights: This is the first meta-analysis of the worldwide prevalence of Cryptosporidium in deer. Cryptosporidium in deer is widespread but unevenly distributed all over the world. The risk factors for the epidemic of Cryptosporidium in deer worldwide were revealed. C. parvum genotype II and C. parvum were the two most common Cryptosporidium species in deer.